2004
DOI: 10.1080/01140671.2004.9514299
|View full text |Cite
|
Sign up to set email alerts
|

Display life ofGentianaflowers is cultivar specific and influenced by sucrose, gibberellin, fluoride, and postharvest storage

Abstract: Gentiana are developing into a significant New Zealand export cut flower crop. The current investigation was undertaken to describe the postharvest characteristics of the cultivars grown in New Zealand, thereby establishing a baseline for selection of new cultivars with superior postharvest performance. Three cultivars were used in the current postharvest investigation, G. triflora 'Nasu NoHakuryo' (a white flowered cultivar), and two blue flowered cultivars, G. triflora 'Late Blue' and G. triflora ' Ashiro No… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 6 publications
0
14
0
Order By: Relevance
“…They concluded that tipburn in Eustoma was an effect of constant high RH that influenced the translocation of Ca 2+ to the leaf tips. Eason et al (2004) investigated the effect of plant age on post-harvest life of cut flowers of G. triflora cv. 'Ashiro No-Ake.'…”
Section: Lightmentioning
confidence: 99%
See 4 more Smart Citations
“…They concluded that tipburn in Eustoma was an effect of constant high RH that influenced the translocation of Ca 2+ to the leaf tips. Eason et al (2004) investigated the effect of plant age on post-harvest life of cut flowers of G. triflora cv. 'Ashiro No-Ake.'…”
Section: Lightmentioning
confidence: 99%
“…In addition, removal of immature shoots was suggested to improve the display quality in cut Eustoma flowers. Eason et al (2004) showed that proper harvest maturity differs for each cultivar in Gentiana flowers. They defined the maturity of stages by the developmental stage of the apical buds.…”
Section: Harvest Maturitymentioning
confidence: 99%
See 3 more Smart Citations